Quantifying the contribution of climate changes and human activities on runoff changes in the Changhua River Basin of Hainan Island - Feixiang Zhang; Wenli Lai; Shuqi Zhang; Wenjie Liu; Shubing Hou; Jie Zhang (Journal of Hydrology: Regional Studies, 2025)
Study region: The Changhua River Basin (CRB) of Hainan Island, China. Study focus: This study quantified the impacts of climate changes and human activities on runoff changes using a novel attribution framework in the CRB. The Variable Infiltration Capacity (VIC) distributed hydrological model was used for numerical experiments to establish a novel framework. The novel framework was employed to assess the impacts of precipitation, temperature, and human activities on runoff at both basin and sub-basin scales. Additionally, the runoff change ratio (RCR, unit: dimensionless) was used to quantify the spatial variability of runoff sensitivity to precipitation and temperature. New hydrological insights for the region: Upon analyzing the numerical experiment results, we discovered that the downstream precipitation contributed significantly, accounting for 79.62 % of runoff changes in the CRB. In contrast, human activities exerted a negative impact on runoff changes (with a contribution rate of −9.07 %). Compared with the upstream region, downstream human activities had caused more drastic changes in runoff. The average RCR in the upstream region (48.56, unit: dimensionless) was approximately 5 times greater than that in the downstream region (10.24). These findings emphasized that the upstream region served as a stabilizing region in the water cycle of the CRB. This study provided a framework for quantifying and separating the impacts of climate changes and human activities on runoff, offering insights for managing water resources.